Design and modeling of an in-wheel two-speed AMT for electric vehicles. (September 2021) - Meng, Dele; Tian, Mengjian; Miao, Liying; Wang, Yuhai; Hu, Jianlong; Gao, Bingzhao
Highlights: Propose a novel in-wheel two-speed automatic manual transmission structure. Integrated design to significantly reduce the unsprung mass. Good system reliability in the harsh working environment within the wheel. No power interruption during gear shifting. Abstract: To improve the performance of the electric vehicles (EVs), significantly reduce unsprung mass, and improve system reliability, in the present paper, the authors propose a novel in-wheel two-speed automatic manual transmission (WH-AMT) structure which weighs only 16.8 kg. The proposed WH-AMT is composed of a high-speed drive motor unit, gear transmission unit, and shift actuator unit. The gear transmission system has no free planet carrier and ring gear, which improves the reliability of the WH-AMT in the harsh working environment within the wheel. Owing to the integrated design in the wheel, the free space in the wheel is increased, and unsprung mass is greatly reduced. In this study, kinematic analysis of the WH-AMT, derivation of its dynamic equations, and development of a simulation model of the shifting process are carried out. The results indicate that there is no power interruption in the WH-AMT during gear shifting, and the shift quality is high, which considerably enhances the power performance of EVs.